Analiza poglądów na rozwój ozów = Analysis of views on the esker genesis - Adam Krupa; Marcin Hojan (Kazimierz Wielki University, 2015)
Krupa Adam, Hojan Marcin. Analiza poglądów na rozwój ozów = Analysis of views on the esker genesis. Journal of Education, Health and Sport. 2015;5(12):717-730. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47019 http://ojs.ukw.edu.pl/index.php/johs/article/view/3410 https://pbn.nauka.gov.pl/works/718157     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.12.2015. Revised 25.12.2015. Accepted: 29.12.2015.     Analiza poglądów na rozwój ozów Analysis of views on the esker genesis   Krupa Adam, Hojan Marcin   Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Polska   Abstrakt W niniejszym artykule zaprezentowano historię poglądów na temat ozów, jak również analizę ich obecnego stanu z odniesieniem do własnych badań i obserwacji na obszarze Pojezierza Krajeńskiego.   Słowa kluczowe: ozy, drenaż lądolodu, środowisko subglacjalne, środowisko inglacjalne, środowisko supraglacjalne.   Abstract This paper presents the history of views on the esker genesis, as well as an analysis of their current state with reference to own research and observations in the area of Krajna Lakeland.   Keywords: eskers, ice sheet drainage, subglacial environment, inglacial environment, supraglacial environment.